2011
DOI: 10.1039/c1sm06102j
|View full text |Cite
|
Sign up to set email alerts
|

Role of superhydrophobicity in the biological activity of fibronectin at the cell–material interface

Abstract: Protein adsorption and cellular behavior depend strongly on the wettability of substrates. Such studies are scarce for surfaces exhibiting extreme values of contact angles. Fibronectin (FN) adsorption and adhesion of MC3T3-E1 cells were investigated on superhydrophobic polystyrene (SH-PS) surfaces and compared with the corresponding smooth polystyrene (PS) substrate and the control glass. The FN surface density was lower on the SH-PS than on PS, and the adsorbed protein showed altered conformation of cell adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 71 publications
5
54
1
Order By: Relevance
“…This fact indicates the influence of wettability on protein adsorption and this effect appears independent from the kind of topography of the rough surfaces. Our findings are in agreement with previous works [20,42,44] and may be explained by a model proposed by Cassie and Baxter [45]. This model postulates that an increase in surface roughness at the micro and nanometer scale leads to superhydrophobicity as a consequence of the fact that liquid can not intrude into the lower regions of the topographic features and a fraction of the surface of the drop in contact with the substrate is suspended by enclosed air pockets.…”
Section: Protein Adsorption On Surfacessupporting
confidence: 82%
See 1 more Smart Citation
“…This fact indicates the influence of wettability on protein adsorption and this effect appears independent from the kind of topography of the rough surfaces. Our findings are in agreement with previous works [20,42,44] and may be explained by a model proposed by Cassie and Baxter [45]. This model postulates that an increase in surface roughness at the micro and nanometer scale leads to superhydrophobicity as a consequence of the fact that liquid can not intrude into the lower regions of the topographic features and a fraction of the surface of the drop in contact with the substrate is suspended by enclosed air pockets.…”
Section: Protein Adsorption On Surfacessupporting
confidence: 82%
“…We performed a BCA assay in order to investigate the effect of surface topography on protein adsorption between topographic cues comparable to what was described elsewhere [39][40][41]. So far just a few studies reported protein adsorption on surfaces exhibiting extreme contact angles [20,42,43]. A comparison of quantitative outcome of these BSA adsorption studies onto smooth and rough surfaces after 24 h is shown in Fig.…”
Section: Protein Adsorption On Surfacesmentioning
confidence: 99%
“…The results indicate that non wettable surfaces exhibit significant more resistance to protein adsorption than wettable paper surfaces, for the all range of initial concentrations explored. Such data are consistent with results previously obtained in other substrates 43,44,46 and may be explained with the Cassie and Baxter model. 47 In fact, if we consider that the air remains in the lower topographical regions of the surface, a decrease in the contact area between the surface and the protein solution will be expected.…”
Section: Resultssupporting
confidence: 93%
“…[18][19][20] Superhydrophobic surfaces prepared by phase separation methods showed low cell adhesion, 18 including substrates prepared using polystyrene. 22 Therefore, we expect that the scaffold spots could be maintained relatively isolated from each other, avoiding cell passage between spots and minimizing the interaction of the platform with the in vivo milieu. All biomaterials patterned in the chips remained attached to the wettable regions of the chip after 24 h of implantation (an example of an explanted chip can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the low cell adhesion reported in superhydrophobic surfaces would improve the independency between spots. 18,22 For the proof-of-concept, we designed an array of 36 combinations of biomaterials from a small library of four materials: chitosan (Chi), alginate (Alg), and two carrageenans: k-carrageenan (k-Carr) and i-carrageenan (i-Carr), the latter having a higher number of sulfate groups. We aimed to study the effect of distinct anionic surfaces combined with Chi, as they were reported to promote higher levels of macrophages and adherent lymphocytes, compared to materials with distinct chemical features.…”
Section: Introductionmentioning
confidence: 99%